# This question is related to Matrix. Solve the following system by operations on the augmented matrix.2y + 3z - 7t = 3 2x + z - 2t = -5 4x + y + z - 5t = -6 y + 2z - 4t = 1

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

You need to remember that you may form the augumented matrix of the system using the coefficients of variables and the constant terms such that:

`[[0,2,3,-7,3],[0,2,1,-2,-5],[4,1,1,-5,-6],[0,1,2,-4,1]]`

You may transform the second element from the fourth row into  a zero multiplying the second column by 2, then subtracting the third column from the second new column such that:

`[[0,4,3,-7,3],[0,4,1,-2,-5],[4,2,1,-5,-6],[0,2,2,-4,1]]`  the second  original column is multiplied by 2

`[[0,1,3,-7,3],[0,3,1,-2,-5],[4,1,1,-5,-6],[0,0,2,-4,1]]`  column 3 is subtracted from column 2

You need to multiply the third column by 2 such that:

`[[0,1,6,-7,3],[0,3,2,-2,-5],[4,1,2,-5,-6],[0,0,4,-4,1]]`

You need to subtract the fourth column from the third new column such that:

`[[0,1,-1,-7,3],[0,3,0,-2,-5],[4,1,-3,-5,-6],[0,0,0,-4,1]]`

You need to convert back this augumented matrix to a system of equations such that:

`y - z - 7t = 3`

`3y - 2t = -5`

`4x + y - 3z - 5t = ` -6

`-4t = 1 =gt t = -1/4`

You may substitute `-1/4`  for t in equation 3y - 2t = -5 such that:

`3y+ 2/4= -5 =gt 3y = -5 - 1/2`

`3y = -11/2 =gt y = -11/6`

You may substitute `-1/4`  for t and`-11/6`  for y  in equation y - z - 7t = 3 such that:

`-11/6- z+ 7/4= 3 =gt z= -11/6 + 7/4 - 3`

`z = (-22 + 21 - 36)/12`

`z = -37/12`

`4x= -y + 3z+ 5t - 6`

`4x = 11/6 - 37/4 - 5/4 - 6`

`4x = (22 - 126 - 72)/12`

`4x = -176/12 =gt x = -44/12 =gt x = -11/3`

Hence, evaluating solutions to system using augumented matrix yields `x = -11/3 ; y = -11/6 ; z = -37/12 ; t = -1/4` .